Optical Glass and Optical Elements

JP7642018B2Active Publication Date: 2025-03-07CDGM OPTICAL GLASS
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023088604
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2023-05-30
Publication Date
2025-03-07
Estimated Expiration
2043-05-30

AI Technical Summary

Benefits of technology

【0021】 本発明の有益な効果は、以下のとおりである。合理的な成分設計により、本発明により得られる光学ガラスは、所望の屈折率とアッベ数を有すると同時に、低い降伏点温度と優れた内在品質を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642018000001
    Figure 0007642018000001
  • Figure 0007642018000002
    Figure 0007642018000002
  • Figure 0007642018000003
    Figure 0007642018000003
Patent Text Reader

Abstract

To provide an optical glass having excellent intrinsic quality and suitable for precision press working.SOLUTION: An optical glass according to the present invention comprises, in wt.%, SiO2: 17-47%, B2O3: 20-50%, Al2O3: 0.5-8%, ZnO: 0.5-8%, RO: 6-45%, La2O3+Y2O3+Gd2O3: 0.5-15%, and Li2O+Na2O+K2O: less than 15%, with ZnO / (La2O3+Y2O3+Gd2O3) of 0.2-4.0, where the RO is the total content of BaO, SrO, CaO, and MgO. Through reasonable component design, the inventive optical glass has a low yield point temperature and excellent intrinsic quality while having an expected refractive index and Abbe number.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to optical glass, and more particularly to optical glass which is excellent in inherent quality and suitable for precision press working, and to a glass preform, an optical element, and an optical device produced from the optical glass. [Background technology]

[0002] Optical glass is a glass material used to manufacture lenses, prisms, mirrors, windows, etc. in optical instruments and mechanical systems. At present, the main method of manufacturing optical glass as optical elements is precision press molding (including direct pressing and secondary pressing). Lenses manufactured using precision pressing technology do not need to be ground and polished, which can reduce raw material consumption, reduce human and material costs, and reduce environmental pollution. Therefore, this technology can be used to mass-produce optical elements at low cost. Precision pressing is the process of press-molding a glass preform with a high-precision mold having a predetermined product shape at a certain temperature and pressure to obtain a glass product with the shape and optical function of the finished product. Precision pressing technology can be used to manufacture a variety of optical glass products, such as spherical lenses, aspherical lenses, prisms, and diffraction gratings.

[0003] With the rapid development of smart driving, face recognition and other technologies, the demand for optical aspherical lenses with a refractive index of 1.57-1.61 and an Abbe number in the range of 58-64 has rapidly increased. In addition, the inherent quality of optical glass is extremely important for its application, and excellent optical glass products are required to have low bubble content or even no bubbles. Optical glass aspherical precision pressing technology can obtain aspherical lenses at low cost, so the development of optical glass with a refractive index of 1.57-1.61, an Abbe number of 58-64, excellent inherent quality, and suitable for precision pressing is of great significance to the development of the optoelectronics industry. Summary of the Invention [Problem to be solved by the invention]

[0004] The technical problem to be solved by the present invention is to provide an optical glass which is excellent in inherent quality and suitable for precision press working. [Means for solving the problem]

[0005] The technical solutions adopted in the present invention to solve the technical problems are as follows:

[0006] (1) Optical glass containing the following by weight: SiO2: 17-47%, B2O3: 20-50%, Al2O3: 0.5-8%, ZnO: 0.5-8%, RO: 6-45%, La2O3+Y2O3+Gd2O3: 0.5-15%, Li2O+Na2O+K2O: less than 15%, ZnO / (La2O3+Y2O3+Gd2O3) is 0.2-4.0, and said RO is the total content of BaO, SrO, CaO, and MgO.

[0007] (2) The optical glass according to (1), further comprising the following components by weight: P2O5: 0-3%, and / or ZrO2: 0-3%, and / or a fining agent: 0-1%, and the fining agent is one or more of Sb2O3, SnO2, Na2SiF6, and K2SiF6.

[0008] (3) An optical glass containing SiO2, B2O3, Al2O3, ZnO and an alkaline earth metal oxide, and further containing the following components by weight: 0.5-15% La2O3+Y2O3+Gd2O3, ZnO / (La2O3+Y2O3+Gd2O3) is 0.2-4.0, and the refractive index n of the optical glass is d is 1.57~1.61, Abbe number ν d The viscosity is 58~64, and the bubble level is A grade or higher.

[0009] (4) The optical glass according to (3), comprising the following components by weight: SiO2: 17-47%, and / or B2O3: 20-50%, and / or Al2O3: 0.5-8%, and / or ZnO: 0.5-8%, and / or RO: 6-45%, and / or Li2O+Na2O+K2O: less than 15%, and / or P2O5: 0-3%, and / or ZrO2: 0-3%, and / or a fining agent: 0-1%, wherein the RO is the total content of BaO, SrO, CaO, and MgO, and the fining agent is one or more of Sb2O3, SnO2, Na2SiF6, and K2SiF6.

[0010] (5) An optical glass according to any one of (1) to (4), comprising the following components in weight percent and satisfying one or more of the following seven conditions: 1) B2O3 / SiO2 is 0.55 to 2.3, preferably B2O3 / SiO2 is 0.7 to 2.0, more preferably B2O3 / SiO2 is 0.8 to 1.8, and even more preferably B2O3 / SiO2 is 1.0 to 1.5; 2) (ZrO2+Al2O3) / B2O3 is 0.05 to 0.4, preferably (ZrO2+Al2O3) / B2O3 is 0.05 to 0.3, more preferably (ZrO2+Al2O3) / B2O3 is 0.05 to 0.25, and even more preferably (ZrO2+Al2O3) / B2O3 is 0.05 to 0.2; 3) BaO / RO is 0.4 to 0.95, preferably BaO / RO is 0.5 to 0.95, more preferably BaO / RO is 0.65 to 0.95, and even more preferably BaO / RO is 0.7 to 0.9; 4) RO / B2O3 is 0.3 to 1.3, preferably RO / B2O3 is 0.4 to 1.2, more preferably RO / B2O3 is 0.5 to 1.0, and even more preferably RO / B2O3 is 0.6 to 0.9; 5) (La2O3+Y2O3+Gd2O3) / RO is 0.05 to 0.9, preferably (La2O3+Y2O3+Gd2O3) / RO is 0.1 to 0.6, more preferably (La2O3+Y2O3+Gd2O3) / RO is 0.1 to 0.4, and even more preferably (La2O3+Y2O3+Gd2O3) / RO is 0.1 to 0.35; 6) ZnO / (La2O3+Y2O3+Gd2O3) is 0.3 to 3.0, preferably ZnO / (La2O3+Y2O3+Gd2O3) is 0.5 to 2.0, more preferably ZnO / (La2O3+Y2O3+Gd2O3) is 0.6 to 1.6; 7) (Na2O+K2O) / Li2O is 0.1 to 1.5, preferably (Na2O+K2O) / Li2O is 0.1 to 1.0, more preferably (Na2O+K2O) / Li2O is 0.2 to 0.8, and even more preferably (Na2O+K2O) / Li2O is 0.25 to 0.65; The RO is the total content of BaO, SrO, CaO and MgO.

[0011] (6) An optical glass according to any one of (1) to (4), comprising the following components by weight: SiO2: 22 to 40%, preferably SiO2: 25 to 38%, and / or B2O3: 22 to 38%, preferably B2O3: 23 to 35%, and / or Al2O3: 1 to 7%, preferably Al2O3: 1 to 6.5%, and / or ZnO: 1 to 7%, preferably ZnO: 1 to 6%, and / or RO: 8 to 40%, preferably RO: 10 to 35%, and / or La2O3+Y2O3+Gd2O3: 1 to 12%, preferably La2O3+Y2O3+Gd2O3. O3: 2-10%, and / or Li2O+Na2O+K2O: less than 12%, preferably Li2O+Na2O+K2O: less than 10%, more preferably Li2O+Na2O+K2O: less than 8%, and / or P2O5: 0-1.5%, and / or ZrO2: 0-2%, preferably ZrO2: 0-1%, and / or fining agent: 0-0.8%, preferably fining agent: 0-0.5%, wherein RO is the total content of BaO, SrO, CaO, and MgO, and the fining agent is one or more of Sb2O3, SnO2, Na2SiF6, and K2SiF6.

[0012] (7) An optical glass according to any one of (1) to (4), comprising the following components by weight: BaO: 5 to 30%, preferably BaO: 6 to 28%, more preferably BaO: 8 to 25%, and / or SrO: 0.5 to 15%, preferably SrO: 0.5 to 13%, more preferably SrO: 0.5 to 12%, and / or CaO: 0 to 10%, preferably CaO: 0 to 9%, more preferably CaO: 0 to 8%, and / or MgO: 0 to 5%, preferably MgO: 0 to 3%, and / or La2O3: 0.5 to 10%, preferably La2O3: 1 to 9%, more preferably Preferably, the composition is La2O3: 1.5 to 8%, and / or Y2O3: 0 to 8%, preferably Y2O3: 0 to 5%, more preferably Y2O3: 0 to 3%, and / or Gd2O3: 0 to 5%, preferably Gd2O3: 0 to 3%, and / or Li2O: 1 to 7%, preferably Li2O: 2 to 6.5%, more preferably Li2O: 3 to 5.5%, and / or Na2O: 0.1 to 7%, preferably Na2O: 0.1 to 6%, more preferably Na2O: 0.5 to 5%, and / or K2O: 0 to 5%, preferably K2O: 0 to 2%, more preferably K2O: 0 to 1%.

[0013] (8) The optical glass according to any one of (1) to (4), further comprising, by weight, the following components: F: 0 to 10%, preferably F: 0 to 5%, and more preferably F: 0 to 3%.

[0014] (9) An optical glass according to any one of (1) to (4), the components of which are free of P2O5, and / or free of MgO, and / or free of Gd2O3, and / or free of F.

[0015] (10) Refractive index n d is 1.57 to 1.61, preferably 1.575 to 1.605, more preferably 1.575 to 1.60, and the Abbe number ν d In the optical glass according to any one of (1) to (4), the refractive index is 58 to 64, preferably 58.5 to 63.5, and more preferably 59 to 63.

[0016] (11) N d Consistency is ±50×10-5 Within, preferably N d Consistency is ±30×10 -5 Within and / or T s Stability within ±5℃, preferably T s The optical glass according to any one of (1) to (4), which has a stability within ±3° C.

[0017] (12) Yield point temperature T s is 610° C. or less, preferably 600° C. or less, more preferably 595° C. or less, and / or a thermal expansion coefficient α 20-300℃ is 85×10 -7 Below 83×10 -7 Less than or equal to 81×10 -7 and / or acid resistance D A is Class 5 or more, preferably Class 4 or more, and / or water resistance D W and / or the foaming degree is Class A or higher, preferably Class A0 or higher, more preferably Class A 00 and / or a stripe C class or higher, preferably B class or higher, and / or a high temperature viscosity at 1200°C of 25 dPaS or lower, preferably 23 dPaS or lower, more preferably 20 dPaS or lower, and / or a high temperature viscosity at 900°C of 35 dPaS or higher, preferably 40 dPaS or higher, more preferably 50 dPaS or higher, and / or an upper crystallization temperature of 1100°C or lower, preferably 1050°C or lower, more preferably 1020°C or lower, and / or a thermoplastic crystallization resistance stability of B class or higher, preferably A class, and / or a refractive index temperature coefficient dn / dt of 6.0×10 -6 / ℃ or less, preferably 5.5×10 -6 / ℃ or less, more preferably 5.0×10 -6 / °C or less.

[0018] (13) A glass preform produced from the optical glass according to any one of (1) to (12).

[0019] (14) An optical element produced from the optical glass according to any one of (1) to (12) or the glass preform according to (13).

[0020] (15) An optical instrument comprising the optical glass according to any one of (1) to (12) and / or the optical element according to (14). Effect of the Invention

[0021] The beneficial effects of the present invention are as follows: Through rational component design, the optical glass obtained by the present invention has a desired refractive index and Abbe number, and at the same time, has a low yield point temperature and excellent intrinsic quality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, the embodiments of the optical glass according to the present invention will be described in detail, but the present invention is not limited to the embodiments described below, and can be practiced by appropriately modifying it within the scope of the object of the present invention. Furthermore, although some parts are omitted, the gist of the present invention is not limited by repeating the description. Hereinafter, the optical glass of the present invention may be simply referred to as glass.

[0023] [Optical glass] The range of the components of the optical glass of the present invention will be described below. In this description, the content and total content of each component will be expressed in weight percent (wt%) unless otherwise specified. In other words, the content and total content of each component will be expressed in weight percent relative to the total weight of the glass material converted into an oxide composition. "Converted into an oxide composition" here refers to the case where the total weight of the oxide material when the oxide, complex salt, hydroxide, etc. used as the raw material of the optical glass composition of the present invention is decomposed and converted into an oxide during melting is taken as 100%.

[0024] Specifically, the numerical ranges described herein include upper and lower limits, and the terms "greater than or equal to" and "less than or equal to" include the endpoints, and all integers and fractions subsumed within the range, but are not limited to the specific values ​​set forth when the range is limited. As used herein, "and / or" is inclusive, e.g., "A and / or B" means A only, B only, or both A and B.

[0025] <Required and optional ingredients> SiO2 is a necessary component of the glass of the present invention, and if its content exceeds 47%, the refractive index and Abbe number of the glass will be lower than the design requirements. On the other hand, the melting temperature of the glass will rise rapidly, and the melting difficulty will increase. In particular, if a large amount of alkali metal oxide components are contained, the corrosion ability of the glass to the melting furnace will rise rapidly, shortening the service life of the furnace body and at the same time, increasing the amount of N d Consistency, T s The stability control becomes more difficult, and there is a risk of increasing the content of bubbles and inclusions in the glass, which may result in failure to meet quality requirements. If the SiO2 content is less than 17%, the chemical stability of the glass rapidly decreases, the water resistance does not meet the design requirements, and mist-like defects are likely to occur on the surface when polishing the aspherical preform, resulting in a decrease in the yield rate of the aspherical preform. Therefore, the SiO2 content is 17-47%, preferably 22-40%, and more preferably 25-38%.

[0026] B2O3 improves the refractive index and Abbe number of glass, and the T s can be reduced. By adding an appropriate amount of B2O3, when it is used to form a glass network together with SiO2, it can further improve the strength of the glass network and the chemical stability of the glass, especially the acid resistance of the glass. If the content of B2O3 exceeds 50%, the glass network will be loosened by B2O3, and the water resistance will be rapidly reduced. During production, B2O3 is usually introduced in the form of boric acid. After a large amount of research by the inventors, it was found that a high content of boric acid accelerates the erosion of the melting furnace during dissolution, while in dissolution, excessive boric acid will intensify volatilization, causing the glass components to change significantly, and the amount of Nd Consistency and T s The stability of the glass decreases rapidly. Moreover, boric acid decomposes to H2O during dissolution, and H2O usually exists in the hot glass liquid in the form of bubbles, and excess boric acid poses a great challenge to the subsequent fining process. When the B2O3 content is less than 20%, the Abbe number and T s However, it is difficult to satisfy the design requirements. Therefore, the content of B2O3 is 20 to 50%, preferably 22 to 38%, and more preferably 23 to 35%.

[0027] As a result of the inventors' research, it was found that in the glass system of the present invention, when the value of B2O3 / SiO2 is greater than 2.3, the time required for the glass liquid to cool from liquid to solid at the molding temperature is greatly increased, and the surface is cooled and hardened first during molding, but the temperature of the middle part is still high, and the difference in time between the surface and the middle part is very large, making it easy to form stripes inside the glass, which is particularly serious in thick products. The glass system of the present invention usually has a molding temperature of 900-1000°C, and if its viscosity is less than 35 dPas within this temperature range, the glass is prone to the above problem, and the stripes do not meet the requirements. Therefore, the value of B2O3 / SiO2 is preferably 2.3 or less, more preferably 2.0 or less, even more preferably 1.8 or less, and even more preferably 1.5 or less. When the value of B2O3 / SiO2 is less than 0.55, the T of the glass is easily formed. s At the same time, the high-temperature viscosity of the glass at 1200°C is difficult to achieve the design goal. In some embodiments, if the high-temperature viscosity of the glass at 1200°C is too large, it is very difficult to eliminate bubbles inside the glass, and the temperature needs to be increased to effectively eliminate the bubbles, but the corrosion ability of the glass liquid to the furnace body at 1200°C or higher increases rapidly. Therefore, the value of B2O3 / SiO2 is preferably 0.55 or more, more preferably 0.7 or more, even more preferably 0.8 or more, and even more preferably 1.0 or more.

[0028] An appropriate amount of Al2O3 can reinforce the glass network, improve the chemical stability of the glass, and increase the high-temperature viscosity of the glass. However, in the glass of the present invention, if more than 8% of Al2O3 is added, the network structure in the glass will rapidly loosen, and in particular, when the B2O3 content is relatively high, corrosion points are likely to occur on the element surface during the polishing process for manufacturing an aspheric preform, and the yield rate will rapidly decrease. In addition, since Al2O3 has a large dispersion, if it is contained in excess, the Abbe number may be lower than the design requirement. If the content is less than 0.5%, the corrosiveness to the furnace body will rapidly increase during the melting process of the glass raw material, and at the same time, the chemical stability, especially the water resistance, will rapidly decrease. Therefore, the content of Al2O3 is limited to 0.5-8%, preferably 1-7%, and more preferably 1-6.5%.

[0029] Adding ZrO2 to glass can reduce the corrosion ability of the glass liquid to the furnace body, extend the service life of the melting furnace, and increase the crystallization resistance of the glass. If the content of ZrO2 exceeds 3%, insoluble matter is likely to appear in the glass, the inherent quality of the glass is deteriorated, and the crystallization resistance of the glass is rapidly deteriorated. Therefore, the content of ZrO2 is 3% or less, preferably 2% or less, and more preferably 1% or less.

[0030] In some embodiments, the use of a mixture of ZrO2 and Al2O3 has a significant effect on the structure state of B2O3, and especially when the content of alkaline earth metal oxides is high, it affects the thermoplastic crystallization resistance of glass. When the value of (ZrO2+Al2O3) / B2O3 is less than 0.05, the improvement of the thermoplastic crystallization resistance of glass is not significant, and when the value of (ZrO2+Al2O3) / B2O3 is greater than 0.4, the thermoplastic crystallization resistance of glass is rather rapidly reduced. Therefore, the value of (ZrO2+Al2O3) / B2O3 is preferably 0.05-0.4, more preferably 0.05-0.3, even more preferably 0.05-0.25, and even more preferably 0.05-0.2.

[0031] The appropriate amount of ZnO significantly improves the refractive index and chemical stability of glass, and reduces the thermal expansion coefficient and T sWhen the ZnO content is less than 0.5%, the above effect is not significant. When the ZnO content exceeds 8%, and particularly when the B2O3 content is relatively high, the Abbe number of the glass is less likely to meet the design requirements, and the bubble removal ability of the glass is reduced. Therefore, the ZnO content is 0.5-8%, preferably 1-7%, and more preferably 1-6%.

[0032] BaO, SrO, CaO, and MgO are alkaline earth metal oxides, and an appropriate amount of alkaline earth metal oxides can increase the refractive index of glass and strengthen the crystallization resistance of glass, but if the total content RO exceeds 45%, the crystallization resistance of glass will rapidly decrease and the glass will even emulsify. Therefore, the total content RO of BaO, SrO, CaO, and MgO is 6-45%, preferably 8-40%, and more preferably 10-35%.

[0033] After extensive experimental research, the inventors found that the order of ability to improve the crystallization resistance of glass is BaO>SrO>CaO>MgO. Therefore, the glass of the present invention preferably uses BaO to improve the refractive index and crystallization resistance of glass. However, if the content exceeds 30%, the water resistance of the glass will rapidly decrease, and bubbles will easily accumulate during melting of the glass and be difficult to eliminate, seriously affecting the stability of the production process, and further increasing the N content of the glass. d Consistency and T s If the BaO content is less than 5%, the refractive index of the glass will be less likely to satisfy the design requirements, and the crystallization resistance stability of the glass will rapidly decrease. Therefore, the BaO content is 5 to 30%, preferably 6 to 28%, and more preferably 8 to 25%.

[0034] SrO forms a synergistic effect with BaO in glass, which effectively improves the crystallization resistance stability of glass and is also advantageous in increasing the refractive index of glass, but if the SrO content is less than 0.5%, the above-mentioned effect is not significant, and if the SrO content exceeds 15%, the synergistic effect of crystallization resistance weakens and the cost of glass rises rapidly. Therefore, the SrO content is 0.5-15%, preferably 0.5-13%, and more preferably 0.5-12%.

[0035] CaO can improve the crystallization resistance of glass, increase the refractive index of glass, rapidly reduce the high-temperature viscosity of glass, and relatively facilitate the removal of bubbles, especially when the relative content of BaO is low, the effect is relatively significant. If the CaO content exceeds 10%, the crystallization resistance of glass will rapidly decrease, and the Abbe number will be lower than the design requirement. Therefore, the CaO content is 0-10%, preferably 0-9%, more preferably 0-8%.

[0036] Although MgO can increase the stability of glass, if its content exceeds 5%, the crystallization resistance of the glass will rapidly decrease and the Abbe number will be lower than the design requirement. Therefore, the MgO content is limited to 5% or less, preferably 3% or less, and more preferably, no MgO is contained.

[0037] In some embodiments, when BaO is used as the alkaline earth metal oxide in the glass of the present invention, and the value of BaO / RO is preferably 0.4 to 0.95, more preferably 0.5 to 0.95, even more preferably 0.65 to 0.95, and still more preferably 0.7 to 0.9, the decrease in the upper limit crystallization temperature of the glass due to the synergistic effect between the alkaline earth metal oxides is most remarkable.

[0038] In some embodiments, the free oxygen provided by the alkaline earth metal oxides can strengthen the B2O3 network, increase its density, and further improve the water resistance and weather resistance of the glass. However, when the value of RO / B2O3 is less than 0.3, the above-mentioned effects are not significant and the thermal expansion coefficient increases. When the value of RO / B2O3 exceeds 1.3, the excess alkaline earth metal components rather destroy the glass network, and the water resistance and weather resistance of the glass rapidly decrease. Therefore, the value of RO / B2O3 is preferably 0.3 to 1.3, more preferably 0.4 to 1.2, even more preferably 0.5 to 1.0, and even more preferably 0.6 to 0.9.

[0039] La2O3 can increase the refractive index of glass and reduce the high-temperature viscosity of glass, but when its content is less than 0.5%, the above effects are not significant. When the La2O3 content exceeds 10%, the acid resistance of glass is rapidly reduced, the thermoplastic crystallization resistance of glass is rapidly reduced, and the T s Therefore, the content of La2O3 is 0.5 to 10%, preferably 1 to 9%, and more preferably 1.5 to 8%.

[0040] Although Y2O3 can be added to glass to increase the refractive index and thermal shock resistance, if its content exceeds 8%, the chemical stability of the glass will rapidly decrease. Therefore, the Y2O3 content is limited to 8% or less, preferably 5% or less, and more preferably 3% or less.

[0041] Although Gd2O3 can increase the refractive index, water resistance and weather resistance of glass, if its content exceeds 5%, the cost of glass will rise rapidly and the crystallization resistance will decrease rapidly. Therefore, the content of Gd2O3 is limited to 5% or less, preferably 3% or less, and more preferably, no Gd2O3 is contained.

[0042] The glass of the present invention takes longer to cool from a high-temperature solution to a solid state than general optical glasses, and then requires two more high-temperature moldings, so adding excess La2O3, Y2O3, and Gd2O3 will rapidly reduce the thermoplastic crystallization resistance of the glass, causing crystallization and further emulsification during thermoplastic processing, leading to a rapid decrease in acid resistance. Therefore, the total content of La2O3, Y2O3, and Gd2O3, La2O3+Y2O3+Gd2O3, is preferably 0.5-15%, more preferably 1-12%, and even more preferably 2-10%.

[0043] In some embodiments, the appropriate amount of La2O3, Y2O3, Gd2O3 and RO can increase the refractive index and Abbe number of the glass, and more importantly, it can reduce the problem of the deterioration of the water resistance of the glass caused by the inclusion of a large amount of RO, while at the same time controlling the acid resistance within the design range, reducing the high-temperature viscosity of the glass, and further reducing the melting temperature of the glass. When the value of (La2O3+Y2O3+Gd2O3) / RO is less than 0.05, the above effects are not significant. When the value of (La2O3+Y2O3+Gd2O3) / RO is more than 0.9, the corrosion of the glass liquid to the furnace body increases, the stability of the glass rapidly decreases, and the T s Therefore, the value of (La2O3+Y2O3+Gd2O3) / RO is preferably 0.05 to 0.9, more preferably 0.1 to 0.6, even more preferably 0.1 to 0.4, and still more preferably 0.1 to 0.35.

[0044] In some embodiments, when components such as La2O3, Y2O3, and Gd2O3 are present in glass, the stability of the glass decreases, and fine bubbles are easily generated during cooling, which may lead to the disposal of the product. As a result of extensive experimental research, the inventors have found that when ZnO coexists with La2O3, Y2O3, and Gd2O3, and the value of ZnO / (La2O3+Y2O3+Gd2O3) is within the range of 0.2 to 4.0, the decrease in stability and bubble content of the glass can be prevented. Therefore, the value of ZnO / (La2O3+Y2O3+Gd2O3) is preferably 0.2 to 4.0, more preferably 0.3 to 3.0, even more preferably 0.5 to 2.0, and even more preferably 0.6 to 1.6.

[0045] Alkali metal oxides (Li2O, Na2O, K2O, etc.) are one of the major components of the glasses of the present invention, and their content and relative content determine the T of the glass. s , which has a significant impact on important indicators such as refractive index, Abbe number, thermal expansion coefficient, chemical stability and crystallization resistance.

[0046] From the viewpoint of the action of single alkali metal oxides, Li2O is the T s When its content is less than 1%, it has the strongest ability to reduce the T s is higher than the design requirement, the chemical stability of the glass is rapidly reduced, and the high-temperature viscosity of the glass is rapidly increased. If the Li2O content exceeds 7%, not only will the corrosion of the glass liquid to the furnace body be rapidly increased, but it will also corrode platinum products during melting, causing platinum inclusions in the glass, and the N content of the glass will be reduced. d Consistency and T s It becomes relatively difficult to control the stability. Therefore, the content of Li2O is 1 to 7%, preferably 2 to 6.5%, and more preferably 3 to 5.5%.

[0047] The appropriate amount of Na2O improves the melting performance of glass and the T sIt can reduce the viscosity of glass at high temperatures, but if the Na2O content is less than 0.1%, the above effects are not significant. If the Na2O content exceeds 7%, the glass corrodes more easily to the furnace body, the chemical stability of the glass decreases, and the thermal expansion coefficient increases rapidly. Therefore, the Na2O content is 0.1-7%, preferably 0.1-6%, and more preferably 0.5-5%.

[0048] If the content of K2O exceeds 5%, the glass network structure is severely destroyed, making it difficult for the water resistance and weather resistance of the glass to meet the design requirements. Therefore, the content of K2O is limited to 5% or less, preferably 2% or less, and more preferably 1% or less.

[0049] As a result of the inventors' research, they found that when three kinds of alkali metal oxides, Li2O, Na2O, and K2O, are mixed and present, a complex synergistic effect occurs, which further affects the erosion of the furnace body, high-temperature viscosity, and refractive index temperature coefficient. By using an aspheric lens, it is possible to realize high-definition imaging while greatly reducing the number of lenses used. However, for lenses used in environments with relatively large temperature differences (such as vehicle-mounted and safety lenses), if the refractive index temperature coefficient of the glass is too large and the number of lenses is small, the "temperature drift" of the lens becomes extremely difficult to control, resulting in serious problems of different imaging quality at different temperatures. In some embodiments, the inventors found that when the value of Li2O+Na2O+K2O is preferably less than 15%, more preferably less than 12%, even more preferably less than 10%, and even more preferably less than 8%, the erosion of the glass liquid to the furnace body is reduced, and the T s It was found that the stability met the design requirements and that the refractive index temperature coefficient of the glass did not exceed the design requirements.

[0050] In some embodiments, when the value of (Na2O+K2O) / Li2O is preferably 0.1 to 1.5, more preferably 0.1 to 1.0, even more preferably 0.2 to 0.8, and even more preferably 0.25 to 0.65, the corrosiveness of the glass liquid to the furnace body is reduced, and T sThe stability meets the design requirements, and the refractive index temperature coefficient of the glass does not exceed the design requirements. More importantly, as long as the above three kinds of alkali metal oxides are within the above range, a lower thermal expansion coefficient can be achieved, which is very important for reducing the lens bursting during aspheric pressing, and greatly improves the freedom and stability of aspheric pressing.

[0051] P2O5 can adjust the refractive index and dispersion of glass. However, in the glass system of the present invention, if its content exceeds 3%, the crystallization resistance of the glass will rapidly decrease, causing a devastating impact on important processes such as glass melting production, blank secondary pressing, and aspheric precision pressing. Therefore, its content is limited to 3% or less, preferably 1.5% or less, and more preferably no P2O5 is contained.

[0052] The right amount of F (fluorine) is the T of glass. s It can significantly reduce the refractive index, increase the Abbe number of the glass, and reduce the use of alkali metal oxides in the glass. When its content exceeds 10%, F is very easy to volatilize during high-temperature melting, and its unit content has a particularly large effect on the refractive index and Abbe number, so N is used in the melting process. d Consistency, T s The stability becomes extremely difficult to control, which has a devastating effect on the subsequent aspheric pressing process. Therefore, the F content is limited to 10% or less, preferably 5% or less, and more preferably 3% or less. s If the above design requirements can be met, it is more preferable that the material does not contain F.

[0053] Sb2O3, SnO2, Na2SiF6, K2SiF6, etc. can be used as fining agents and are advantageous in increasing the foaming rate of the glass, and when present alone or in combination, the amount is 1% or less, preferably 0.8% or less, more preferably 0.5% or less.

[0054] In addition to optimizing the meltability of glass and improving the porosity of glass through component design, similar high-viscosity silicate glasses usually optimize the meltability and porosity of glass by introducing oxide components in the form of nitrates. Nitrates convert most of the nitrogen element into NO during the melting process. X Nitrogen oxides are released into the atmosphere as gas, which causes great damage to human health, and long-term inhalation is a risk of causing lung cancer. Therefore, the inventors have been engaged in research to reduce the emission of nitrogen oxides while ensuring the melting performance of glass. After extensive experimental research, the inventors have found that when nitrates are introduced in the form of KNO3 and Ba(NO3)2 and mixed with the above-mentioned fining agents (Sb2O3, SnO2, Na2SiF6, K2SiF6, etc.), the bubble degree of glass meets the quality requirements and the emission of nitrogen oxides can be reduced to a lower level. By conversion, the N (nitrogen) element content in the glass raw material (N element introduction amount when melting 100 kg of theoretical glass / 100 kg glass weight x 100%) is less than 2.0%, preferably less than 1.5%, and more preferably less than 1.0%.

[0055] <Ingredients that should not be included> In the glass of the present invention, even when oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained alone or in combination in small amounts, the glass is colored and specific wavelengths in the visible light region are absorbed, weakening the visible light transmission effect of the present invention. Therefore, it is preferable that optical glasses which require wavelength transmittance in the visible light region in particular not actually contain such oxides.

[0056] In recent years, there has been a trend to restrict the use of oxides of Th, Cd, Tl, Os, Be and Se as harmful chemicals, and environmental protection efforts are required not only in the glass manufacturing process but also in the processing process and treatment of the finished product. Therefore, when the impact on the environment is important, it is preferable that they are not included except for unavoidable contamination. This makes the optical glass actually free of substances that pollute the environment. Therefore, the optical glass of the present invention can be manufactured, processed and disposed of without taking special environmental measures. In consideration of the environment, it is preferable that the optical glass of the present invention does not include As2O3 and PbO.

[0057] The terms "not added," "not included," and "0%" used herein mean that the component was not intentionally added as a raw material for the glass of the present invention. However, impurities or components that are not intentionally added as raw materials and / or equipment for producing the glass may be present in small or trace amounts in the final glass, and are also covered by the present invention.

[0058] The performance of the optical glass of the present invention will be described below. <Refractive index and Abbe number> The refractive index of optical glass (n d ) and Abbe number (ν d ) is tested according to the method specified in GB / T7962.1-2010. In some embodiments, the refractive index (n d ) is 1.57 to 1.61, and the refractive index (n d ) is 1.575 to 1.605, more preferably the refractive index (n d In some embodiments, the Abbe number (ν d ) is 58 to 64, preferably the Abbe number (ν d ) is 58.5 to 63.5, more preferably the Abbe number (ν d ) is 59-63.

[0059] <N d Consistency> During production, five glass samples were extracted every 24 hours, annealed, and then measured for refractive index (N d ) is measured, and the difference from the standard value is N d In some embodiments, the N of the optical glass of the present invention is d Consistency is ±50×10 -5 Within, preferably N d Consistency is ±30×10 -5 Within.

[0060] <Yield point temperature> Yield point temperature of optical glass (T s ) is measured according to the method specified in GB / T7962.16-2010. In some embodiments, the yield point temperature (T s ) is 610°C or less, preferably the yield point temperature (T s ) is 600°C or less, and more preferably the yield point temperature (T s ) is 595°C or less.

[0061] <T s Stability> During production, five glass samples were extracted every 24 hours, annealed, and then tested for T according to the method specified in GB / T7962.16-2010. s The difference between the standard value and the s In some embodiments, the T of the optical glass of the present invention s Stability within ±5℃, preferably T s Stability is within ±3℃.

[0062] <Thermal expansion coefficient> Thermal expansion coefficient of optical glass (α 20-300℃ ) is data measured at 20 to 300°C according to the method specified in GB / T7962.16-2010. In some embodiments, the thermal expansion coefficient (α 20-300℃ ) is 85 x 10 -7 Hereinafter, the thermal expansion coefficient (α 20-300℃ ) is 83 x 10 -7 Hereinafter, more preferably, (α 20-300℃ ) is 81 x 10-7 The following is the result.

[0063] <Acid resistance stability> Acid resistance stability of optical glass (D A ) (powder method) is tested according to the method specified in GB / T17129. In this specification, acid resistance stability may be referred to as acid resistance. In some embodiments, the acid resistance stability (D A ) is 5 or more, and preferably acid resistance (D A ) is Class 4 or higher.

[0064] <Water resistance stability> Water resistance stability of optical glass (D W ) (powder method) is tested according to the method specified in GB / T17129. In this specification, water resistance stability may be referred to as water resistance. In some embodiments, the water resistance stability (D W ) is Class 4 or higher, and preferably water resistance (D W ) is Class 3 or higher.

[0065] <Bubble content> The porosity of the optical glass is tested according to the method specified in GB / T7962.8-2010. In some embodiments, the porosity of the optical glass of the present invention is Class A or higher, preferably Class A0 or higher, more preferably Class A1 or higher. 00 It is of class.

[0066] <Stripe> The stripes of the optical glass are confirmed by comparing a standard sample with a stripe meter consisting of a point light source and a lens from the direction in which the stripes are most visible. There are four grades. For details, see Table 1. In some embodiments, the stripes of the optical glass of the present invention are C grade or higher, preferably B grade or higher. [Table 1]

[0067] <High temperature viscosity> The high temperature viscosity of optical glasses is tested according to the following method: using a THETA Rheotronic II high temperature viscometer in a rotational method, the numerical unit is dPaS (poise), and the smaller the numerical value, the smaller the viscosity. In some embodiments, the high temperature viscosity of the optical glasses of the present invention at 1200°C is 25 dPaS or less, preferably 23 dPaS or less, and more preferably 20 dPaS or less at 1200°C. In some embodiments, the high temperature viscosity of the optical glasses of the present invention at 900°C is 35 dPaS or more, preferably 40 dPaS or more, and more preferably 50 dPaS or more at 900°C.

[0068] <Crystallization resistance> Glass applied to aspheric precision press processing requires three stages of high-temperature processing, including high-temperature molding, high-temperature secondary press processing, and high-temperature precision press processing, so the crystallization resistance stability of the glass is very important. Crystallization resistance stability is divided into two types: one is the crystallization resistance during the process of cooling the glass liquid from liquid to solid state, which is represented by the upper crystallization temperature limit, and the crystallization resistance during high-temperature secondary press processing and high-temperature precision press processing can be represented by a thermoplastic crystallization resistance test. The crystallization resistance (or glass stability) described in this specification generally refers to the above two types of crystallization resistance.

[0069] Crystallization resistance stability can be divided into two types. One is the crystallization resistance during the process of cooling the glass liquid from a high-temperature (1000-1200℃) liquid to a solid state, which is represented by the upper crystallization temperature. The crystallization resistance during high-temperature secondary pressing and high-temperature precision pressing can be represented by the thermoplastic crystallization resistance test.

[0070] The test method for the upper crystallization temperature is as follows: the temperature gradient furnace method is used to measure the crystallization performance of glass, and a glass sample of 180×10×10 mm is polished on the side, placed in a gradient temperature (10°C / cm) furnace to heat up to a maximum temperature range of 1400°C, kept warm for 4 hours, then taken out and naturally cooled to room temperature, and the crystallization state of the glass is observed under a microscope. The maximum temperature at which devitrification of the glass occurs is the upper crystallization temperature of the glass. In some embodiments, the upper crystallization temperature of the optical glass of the present invention is 1100°C or less, preferably 1050°C or less, and more preferably 1020°C or less.

[0071] The thermoplastic crystallization stability test method is as follows: A sample processed to 20 x 20 x 10 mm is polished on both sides and the sample is s It is placed in a crystallization furnace at +200°C for 30 minutes, removed and cooled, and then the two large surfaces are polished. The crystallization resistance of the glass is judged according to Table 2, with Grade A being the best and Grade E being the worst. In some embodiments, the thermoplastic crystallization resistance of the optical glass of the present invention is Grade B or above, preferably Grade A, and has excellent crystallization resistance. [Table 2]

[0072] <Temperature coefficient of refractive index> The refractive index temperature coefficient (dn / dt) of optical glass in the range of 40 to 60 degrees Celsius (d line dn / dt relative (10 -6 In some embodiments, the refractive index temperature coefficient (dn / dt) of the optical glass of the present invention is 6.0×10 -6 / ℃ or less, preferably 5.5×10 -6 / ℃ or less, more preferably 5.0×10 -6 / ℃ or less.

[0073] [Manufacturing method] The manufacturing method of the optical glass of the present invention is as follows: The glass of the present invention is manufactured by conventional raw materials and conventional processes, including but not limited to oxides, hydroxides, fluorides, various salts (carbonates, nitrates, sulfates, phosphates, metaphosphates), boric acid, etc., and after blending by a conventional method, the prepared furnace material is put into a melting furnace (such as a platinum, gold or platinum alloy crucible) at 1400 to 1550 ° C. and melted. Then, it is clarified and homogenized to obtain a homogeneous molten glass without bubbles or unmelted materials, and this molten glass is cast into a mold and annealed. Those skilled in the art can appropriately select the raw materials, manufacturing methods and process parameters according to the actual needs.

[0074] [Glass preforms and optical elements] A glass preform can be manufactured from the optical glass prepared by using a press molding method such as direct drop molding, polishing, or hot press molding. That is, a precision glass preform can be manufactured from molten optical glass by direct precision drop molding, a glass preform can be manufactured by mechanical processing such as grinding or polishing, or a preform blank for press molding can be manufactured using optical glass, and the preform blank can be hot pressed and polished to manufacture a glass preform. It should be noted that the manufacturing method of the optical preform is not limited to the above-mentioned methods.

[0075] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferable to form a blank from the optical glass of the present invention and use this blank to carry out hot press molding, precision press molding, or the like to produce optical elements such as lenses and prisms.

[0076] The optical preform and optical element of the present invention are both formed from the optical glass of the present invention. The optical preform of the present invention has the excellent properties of optical glass, and the optical element of the present invention has the excellent properties of optical glass, making it possible to provide optical elements such as various lenses and prisms with high optical value.

[0077] Examples of lenses include various lenses with spherical or aspherical lens surfaces, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, etc. The lenses according to the present invention further include lenses of automobile lamps.

[0078] [Optical equipment] The optical elements made of the optical glass of the present invention can be used in the manufacture of optical instruments, including, but not limited to, photographic devices, imaging devices, projection devices, display devices, vehicle-mounted devices (including lamps), and surveillance devices. EXAMPLES

[0079] <Optical glass examples> In order to further clearly illustrate the technical solutions of the present invention, the following non-limiting examples are provided.

[0080] In the present examples, the above-mentioned optical glass manufacturing method was used to obtain optical glasses having the compositions shown in Tables 3 to 5. In addition, the properties of each glass were measured by the test methods described in the present invention, and the results are shown in Tables 3 to 5. [Table 3]

[0081] [Table 4]

[0082] [Table 5]

[0083] <Glass preform example> The glasses obtained in Examples 1 to 20 of the optical glass are subjected to polishing, hot press molding, precision press molding, or other press molding means to produce various lenses, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, as well as preforms such as prisms.

[0084] <Optical element examples> The preform obtained in the above optical preform example is tempered to fine-tune the refractive index while reducing distortion within the glass so that the optical properties, such as the refractive index, reach the desired values.

[0085] Each preform is then ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. An anti-reflective coating can also be applied to the surfaces of the obtained optical elements.

[0086] <Optical equipment examples> The optical elements manufactured according to the above optical element embodiments can be used in imaging devices, sensors, microscopes, medical technology, digital projection, communication, optical communication technology / information transmission, optics / illumination in the automotive field, photolithography technology, excimer lasers, wafers, computer chips and integrated circuits and electronic devices containing such circuits and chips, or imaging equipment and devices in the automotive field by forming optical parts or components using one or more optical elements according to optical design.

Claims

1. SiO by weight 2 : 17-47%, B 2 O 3 :20~50%, Al 2 O 3 :0.5~8%, ZnO:0.5~8%, RO:6~45%, La 2 O 3 +Y 2 O 3 +Gd 2 O 3 :0.5~15%, Li 2 O+Na 2 O+K 2 O: less than 15%, ZnO / (La 2 O 3 +Y 2 O 3 +Gd 2 O 3 ): 0.2-4.0, BaO / RO: 0.65-0.95, (Na 2 O+K 2 O) / Li 2 O: 0.1 to 0.68, The RO is the total content of BaO, SrO, CaO, and MgO. Optical glass.

2. P in weight percent 2 O 5 : 0 to 3%, and / or ZrO 2 : 0-3%, and / or clarifier: 0-1%, The fining agent is Sb 2 O 3 , SnO 2 , Na 2 SiF 6 , K 2 SiF 6 One or more of the following: The optical glass according to claim 1 .

3. SiO 2 , B 2 O 3 , Al 2 O 3 ZnO and an alkaline earth metal oxide, SiO 2 : 17-47%, B 2 O 3 : 20-50%, Al 2 O 3 : 0.5-8%, ZnO: 0.5-8%, RO: 6-45%, La 2 O 3 +Y 2 O 3 +Gd 2 O 3 : 0.5 to 15%, Li 2 O + Na 2 O + K 2 O: less than 15%, ZnO / (La 2 O 3 +Y 2 O 3 +Gd 2 O 3 ): 0.2-4.0, BaO / RO: 0.65-0.95, (Na 2 O+K 2 O) / Li 2 O: 0.1 to 0.68, The RO is the total content of BaO, SrO, CaO, and MgO, The refractive index n of the optical glass d is 1.57 to 1.61, Abbe number ν d is 58-64, and the bubble level is A grade or higher. Optical glass.

4. P in weight percent 2 O 5 : 0 to 3%, and / or ZrO 2 : 0-3%, and / or clarifier: 0-1%, The RO is the total content of BaO, SrO, CaO, and MgO, The fining agent is Sb 2 O 3 , SnO 2 , Na 2 SiF 6 , K 2 SiF 6 One or more of the following: The optical glass according to claim 3.

5. The components expressed in weight percent are: 1) B 2 O 3 / SiO 2 is 0.55 to 2.3; 2) (ZrO 2 +Al 2 O 3 ) / B 2 O 3 は0.05~0.4; 3) R / B 2 Oh 3 は0.3~1.3; () 2 O 3 +Y 2 O 3 +Gd 2 O 3 ) / ROは0.05~0.9; 5) ZnO / (La 2 O 3 +Y 2 O 3 +Gd 2 O 3 ) satisfies one or more of the following criteria: 0.3 to 3.0; The RO is the total content of BaO, SrO, CaO, and MgO. The optical glass according to any one of claims 1 to 4.

6. The components expressed in weight percent are: 1) B 2 O 3 / SiO 2 is 0.7-2.0; 2) (ZrO 2 +Al 2 O 3 ) / B 2 O 3 は0.05~0.3; 3) R / B 2 Oh 3 は0.4~1.2; () 2 O 3 +Y 2 O 3 +Gd 2 O 3 ) / ROは0.1~0.6; 5) ZnO / (La 2 O 3 +Y 2 O 3 +Gd 2 O 3 ) satisfies one or more of the following criteria: 0.5 to 2.0; The RO is the total content of BaO, SrO, CaO, and MgO. The optical glass according to any one of claims 1 to 4.

7. The components expressed in weight percent are: 1) B 2 O 3 / SiO 2 is 0.8-1.8; 2) (ZrO 2 +Al 2 O 3 ) / B 2 O 3 は0.05~0.25; 3) BaO / RO is 0.65 to 0.9; 4) R / B 2 Oh 3 は0.5~1.0; () () 2 O 3 +Y 2 O 3 +Gd 2 O 3 ) / ROは0.1~0.4; () () 2 O 3 +Y 2 O 3 +Gd 2 O 3 )は0.6~1.6; 7) (Na 2 O+K 2 O) / Li 2 O satisfies one or more of the following criteria: 0.2 to 0.68; The RO is the total content of BaO, SrO, CaO, and MgO. The optical glass according to any one of claims 1 to 4.

8. The components expressed in weight percent are: 1) B 2 O 3 / SiO 2 is 1.0 to 1.5; 2) (ZrO 2 +Al 2 O 3 ) / B 2 O 3 は0.05~0.2; 3) BaO / RO is 0.7-0.9; 4) R / B 2 Oh 3 は0.6~0.9; () () 2 O 3 +Y 2 O 3 +Gd 2 O 3 ) / ROは0.1~0.35; 6) (Na 2 O+K 2 O) / Li 2 O satisfies one or more of the following criteria: 0.25 to 0.65; The RO is the total content of BaO, SrO, CaO, and MgO. The optical glass according to any one of claims 1 to 4.

9. SiO by weight 2 : 22 to 40%, and / or B 2 O 3 : 22 to 38%, and / or Al 2 O 3 : 1 to 7%, and / or ZnO: 1 to 7%, and / or RO: 8 to 40%, and / or La 2 O 3 +Y 2 O 3 +Gd 2 O 3 : 1 to 12%, and / or Li 2 O+Na 2 O+K 2 O: less than 12% and / or P 2 O 5 : 0 to 1.5%, and / or ZrO 2 : 0-2%, and / or clarifier: 0-0.8%, The RO is the total content of BaO, SrO, CaO, and MgO, and the fining agent is Sb 2 O 3 , SnO 2 , Na 2 SiF 6 , K 2 SiF 6 One or more of the following: The optical glass according to any one of claims 1 to 4.

10. SiO by weight 2 : 25 to 38%, and / or B 2 O 3 : 23 to 35%, and / or Al 2 O 3 : 1 to 6.5%, and / or ZnO: 1 to 6%, and / or RO: 10 to 35%, and / or La 2 O 3 +Y 2 O 3 +Gd 2 O 3 : 2 to 10%, and / or Li 2 O+Na 2 O+K 2 O: less than 8% and / or ZrO 2 : 0-1%, and / or clarifier: 0-0.5%, The RO is the total content of BaO, SrO, CaO, and MgO, and the fining agent is Sb 2 O 3 , SnO 2 , Na 2 SiF 6 , K 2 SiF 6 One or more of the following: The optical glass according to any one of claims 1 to 4.

11. In weight percent, BaO: 5 to 30%, and / or SrO: 0.5 to 15%, and / or CaO: 0 to 10%, and / or MgO: 0 to 5%, and / or La 2 O 3 : 0.5 to 10%, and / or Y 2 O 3 : 0 to 8%, and / or Gd 2 O 3 : 0 to 5%, and / or Li 2 O: 1 to 7% and / or Na 2 O: 0.1 to 7% and / or K 2 O: Contains 0-5% of the ingredient The optical glass according to any one of claims 1 to 4.

12. By weight, BaO: 8 to 25%, and / or SrO: 0.5 to 12%, and / or CaO: 0 to 8%, and / or MgO: 0 to 3%, and / or La 2 O 3 : 1.5 to 8%, and / or Y 2 O 3 : 0 to 3%, and / or Gd 2 O 3 : 0 to 3%, and / or Li 2 O: 3 to 5.5% and / or Na 2 O: 0.5 to 5% and / or K 2 O: Contains 0-1% of the ingredient The optical glass according to any one of claims 1 to 4.

13. Further contains F: 0 to 5% by weight The optical glass according to any one of claims 1 to 4.

14. The refractive index n of the optical glass d is 1.57 to 1.61, Abbe number ν d is 58 to 64 The optical glass according to any one of claims 1 to 4.

15. The refractive index n of the optical glass d is 1.575 to 1.60, Abbe number ν d is 59-63 The optical glass according to any one of claims 1 to 4.

16. The optical glass N d Consistency is ±50 x 10 -5 Within and / or T s Stability within ±5°C and / or yield temperature T s is 610°C or less, and / or the thermal expansion coefficient α 20-300℃ is 85 x 10 -7 and / or acid resistance stability D A Class 5 or higher and / or water resistance D W Class 4 or higher, and / or the degree of cellularity is Class A or higher, and / or the stripes are Class C or higher, and / or the high temperature viscosity at 1200°C is 25 dPaS or lower, and / or the high temperature viscosity at 900°C is 35 dPaS or higher, and / or the upper crystallization temperature is 1100°C or lower, and / or the thermoplastic crystallization resistance stability is Class B or higher, and / or the refractive index temperature coefficient dn / dt is 6.0×10 -6 / ℃ or less The optical glass according to any one of claims 1 to 4.

17. The optical glass N d Consistency is ±30 x 10 -5 Within and / or T s Stability within ±3°C and / or yield temperature T s is 595°C or less, and / or the thermal expansion coefficient α 20-300℃ is 81 x 10 -7 and / or acid resistance stability D A Class 4 or higher and / or water resistance D W Class 3 or higher and / or foaming degree A 00 and / or the stripe is B class or higher, and / or the high temperature viscosity at 1200°C is 20 dPaS or lower, and / or the high temperature viscosity at 900°C is 50 dPaS or higher, and / or the upper crystallization temperature is 1020°C or lower, and / or the thermoplastic crystallization resistance stability is A class, and / or the refractive index temperature coefficient dn / dt is 5.0 x 10 -6 / ℃ or less The optical glass according to any one of claims 1 to 4.

18. A glass preform made from the optical glass according to any one of claims 1 to 4.

19. An optical element manufactured from the optical glass according to any one of claims 1 to 4.

20. An optical instrument comprising the optical glass according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Optical glass for precision profiling

    CN101215083A

  • Environment-friendly low-melting-point optical glass

    CN102476915A

  • Optical glass, glass prefabticated member, optical element and optical instrument

    CN109250901A

  • Optical glass

    JP1996012368A

  • Production of glass optical element

    JP1996277127A